Work Life Balance and Level of Satisfaction Among Women Teachers Assigned In The Northernmost Part of The Province of Surigao Del Sur, Philippines - Mercado, Jillard O. (UI Scholars Hub, 2019)
Research Aims - This research intends to study the extent of work-life balance and the level of satisfaction among women teachers assigned in the northernmost part of the province of Surigao del Sur and to determine if there is a significant relationship between them. Design/methodology/approach - This study used the descriptive normative and correlation method. The adopted questionnaire was modified and used. A total of 226 women teachers were chosen as respondent but only 210 participated. The data gathered from the questionnaire were tallied, tabulated, analyzed and presented in tables. Research Findings - The result shows that majority of the teachers answered “moderate extent” to the work life balance under personal and work environment and mostly “satisfied” on the level of satisfaction. It concludes that there is a significant relationship between the work life balance and level of satisfaction. Theoretical Contribution/Originality – Significant relationship between the work life balance and the level of satisfaction were tested in this study and showed that there is a relationship of work and life balance and the level of satisfaction among women teachers assigned in the northernmost part of the province of Surigao del Sur. Managerial Implications in the South Asian Context – Managers or administrators in Southeast Asian context especially in the education sector have to consider not only the work of their women employees in their institution but also their personal life because once these two balanced; this could lead to high level of job satisfaction. As an effect, this could heighten the level of commitment and their loyalty. Research limitations and recommendation – This study limits only to women teachers assigned in the northernmost part of the province of Surigao del sur. This paper offers for further research to other sectors.